Press in a political year - Benni Setiawan (Universitas Negeri Yogyakarta, 2023)
Although it is difficult for the press to move away from many interests, the breath of news should continue to be on a footing of truth and humanity. This breath can guarantee an upright democracy, as one of the functions of the press is the fourth pillar of democracy. However, if the press continues to be in the shadow of certain political parties and candidates, this will alarm the growth and development of a dignified life. The press, which should be a torch of civilization, has instead become a mouthpiece for specific political forces. The power of the press should be for the benefit of life, not just to satisfy the thirst for power seekers.